Change in Anthropometric Parameters of the Posture of Students of Physiotherapy after Three Years of Professional Training. (25th December 2013) - Glista, Joanna; Pop, Teresa; Weres, Aneta; Czenczek-Lewandowska, Ewelina; Podgórska-Bednarz, Justyna; Rykała, Justyna; Leszczak, Justyna; Sowa, Karolina; Rusek, Wojciech
Abstract : Introduction and Aim . A physiotherapist's occupation requires high physical fitness and a properly functioning neuromuscular system. Working with patients is not always performed in accordance with the rules of work ergonomics. The aim of this paper was to verify the possible changes in the posture of students of physiotherapy after three years of professional training. Material and Methods . The sample group consisted of 30 randomly chosen students of physiotherapy. Each person was examined twice (at the age of 20 and at the age of 23). Both examinations were performed by the same researcher. The ultrasound system ZEBRIS Pointer was used for the examination; 17 parameters were analyzed in sagittal projection, frontal projection, and transversal projection. Results . Statistical analysis revealed positive correlations between the 10 parameters in examination 1 and examination 2 which means that a person with a relatively higher level of obliquity in examination number 1 also had slightly different values in an examination conducted three years later. Conclusion . Studying physiotherapy and physical work with patients resulted in a considerable worsening of the students' posture. It is advisable to educate students on ergonomics and the rules of safety and hygiene while working as a physiotherapist in order to protect the therapists' health.